Byline - Akbar, M. J. (New Delhi : Chronicle Books ; Bangalore : Distributed by Orient Longman Ltd., 2003)
Articles of M.J. Akbar, noted journalist of India; focus on his travels world over.
Keywords: Akbar, M. J. -- Travel; Journalists -- India -- Biography